Collagen mineralization with lepidocrocite via Fe(OH)2 addition. Issue 6 (26th January 2022) - Oosterlaken, Bernette M.; van Rijt, Mark M. J.; Friedrich, Heiner; de With, Gijsbertus
Abstract : Intrafibrillar lepidocrocite platelets are shown to be present throughout the entire thickness of collagen fibrils using electron tomography. Abstract : The mineralization of collagen in vitro has been extensively investigated for hydroxyapatite, silica, calcium carbonate and lepidocrocite (γ-FeOOH). Henceforth, it is interesting to investigate whether collagen also could serve as a generic mineralization template for other minerals, like magnetite. To this end, and inspired by the partial oxidation approach, first a ferrous hydroxide (Fe(OH)2 ) intermediate is synthesized via the titration of base to a solution of Fe 2+ . Subsequently, the Fe(OH)2 is mixed with collagen fibrils and poly(aspartic acid) is added to promote the formation of intrafibrillar crystals. Platelet-shaped lepidocrocite crystals being present throughout the entire thickness of the collagen fibrils can be realized, as was confirmed with electron tomography. The formation of lepidocrocite, which is an Fe 3+ compound, is hypothesized to be induced via oxidation of the Fe 2+ species and, therefore, the oxygen concentration during titration, TEM sample preparation and drying of TEM samples are investigated. Although the reaction is sensitive to small changes in experimental conditions, highly mineralized collagen fibers can be realized.